Effect of Canagliflozin on Blood Pressure and Adverse Events Related to Osmotic Diuresis and Reduced Intravascular Volume in Patients With Type 2 Diabetes Mellitus. Issue 12 (20th October 2014) - Weir, Matthew R.; Januszewicz, Andrzej; Gilbert, Richard E.; Vijapurkar, Ujjwala; Kline, Irina; Fung, Albert; Meininger, Gary
<x xml:space="preserve">Abstract</x> The effects of canagliflozin, a sodium glucose co‐transporter 2 inhibitor, on blood pressure (BP) and osmotic diuresis– and intravascular volume reduction–related adverse events (AEs) were evaluated using pooled data from four placebo‐controlled, phase 3 studies in patients with type 2 diabetes mellitus (T2DM; N=2313). At baseline, 1332 (57.6%) patients were taking an antihypertensive medication. Canagliflozin 100 mg and 300 mg provided reductions (95% confidence interval [CI]) from baseline in systolic BP (SBP) compared with placebo (−4.3 mm Hg [−5.0 to −3.5], −5.0 mm Hg [−5.8 to −4.2], and −0.3 mm Hg [−1.2 to 0.5], respectively) and in diastolic BP (DBP; −2.5 mm Hg [−2.9 to −2.0], −2.4 mm Hg [−2.9 to −1.9], and −0.6 mm Hg [−1.1 to −0.02], respectively). Placebo‐subtracted reductions (95% CI) in SBP with canagliflozin 100 mg and 300 mg were −4.0 mm Hg (−5.1 to −2.8) and −4.7 mm Hg (−5.8 to −3.5) and reductions in DBP were −1.9 mm Hg (−2.6 to −1.2) and −1.9 mm Hg (−2.6 to –1.1), respectively. Compared with the overall population, patients with elevated baseline SBP (≥140 mm Hg) had numerically greater absolute SBP reductions (95% CI) with canagliflozin 100 mg and 300 mg and placebo (−12.8 mm Hg [−15.2 to −10.5], −14.2 mm Hg [−16.4 to −12.0], and −6.8 mm Hg [−9.1 to −4.5], respectively). Numerically greater DBP reductions were seen in patients with DBP ≥90 mm Hg at baseline (−5.9 mm Hg [−8.2 to −3.6], −9.0 mm Hg [−11.1 to −6.9], and −7.4 mm Hg [−9.6 to −5.1], respectively). In patients with elevated SBP at baseline, placebo‐subtracted reductions (95% CI) in SBP with canagliflozin 100 mg and 300 mg were −6.0 mm Hg (−9.1 to −2.9) and −7.4 mm Hg (−10.4 to −4.4), respectively. Placebo‐subtracted changes in DBP were 1.5 mm Hg (−1.6 to 4.5) and −1.6 mm Hg (−4.5 to 1.2), respectively, in those with elevated DBP at baseline. Canagliflozin 100 mg and 300 mg were associated with increased incidence of osmotic diuresis–related AEs (eg, pollakiuria [increased urine volume] and polyuria [increased urine frequency]) vs placebo (6.7%, 5.6%, and 0.8%). The incidence of intravascular volume reduction–related AEs (eg, orthostatic hypotension and postural dizziness) was low across groups (1.2%, 1.3%, and 1.1%). In summary, canagliflozin was associated with reduced BP in patients with T2DM across a range of baseline BPs, with increased incidence of AEs related to osmotic diuresis but not intravascular volume reduction.